Dialectic relationship of the head of the state with the parliament in the mechanism of restraints and balances in Ukraine - Kaminska, Olena; Fedorchenko, Oleh; Alekseyenko, Anna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
Ukraine is a democratic and legal State that involves the division of State power into relatively independent branches. The article emphasizes the relativity of such independence, which is explained by the interaction of the branches of power, their mutual influence, and therefore the dialectical relationship between them. So, to build a truly democratic legal State, it is necessary to clearly delimit and constitutionally determine the duties of each branch of power.The article is dedicated to the study of interaction and distribution of powers between the two leading bodies in the State mechanism: the President and the Parliament. These institutions are the result of direct democracy, i. e., they are formed by popular vote. The sovereignty and the right of the Ukrainian people to govern their State are realized with their help. The activity of these bodies has to complement each other, and therefore their powers do not have to conflict with each other.The dialectical relationship of these bodies is primarily provided for by the Constitution. Yes, the Verkhovna Rada represents exclusively the Ukrainian people, the President does not have such powers. Instead, the President represents the State, and the Verkhovna Rada does not. The Verkhovna Rada is the legislative branch of power, and the President belongs neither to the legislative, nor executive, nor judicial branch of power. The Parliament has much more powers in the legislative sphere, but the President also performs a legislative function. Its realization means the interaction of the two higher State bodies, and therefore, a dialectical relationship between them.The close interaction between the President of Ukraine and the Verkhovna Rada of Ukraine can be seen in the formation of the executive power system. In particular, though the personal composition of the Cabinet of Ministers is appointed by the Parliament, the President submits candidacies for the post of the Prime Minister and two ministers (of Foreign Affairs and Defense).There is also an interaction between the Parliament and the President, who has the most of powers, in the sphere of judicial power, for instance in the formation, reorganization and liquidation of courts. However, both the Parliament and the President form the Constitutional Court of Ukraine together appointing to positions a third of its members.So, the Verkhovna Rada of Ukraine and the President of Ukraine have joint powers in different areas. These powers have been proved to be carefully verified and precisely established at the legislative level. On one hand, they cannot contradict each other, because the government in Ukraine is unified. On the other hand, to ensure independence, they both have sufficient autonomy in the performance of their duties. In addition, to prevent the predominance of one branch of government over the other, they have joint powers, which are the levers of the system of restraints and balances.The successful exercise of their powers by the President of Ukraine and the Verkhovna Rada of Ukraine is achieved due to their interaction and to some extent interdependence.